RHYTHMICS IN THE SYSTEM OF CONTINUOUS CHOREOGRAPHIC EDUCATION: HISTORICAL AND PEDAGOGICAL ASPECTS - Blagova, Tatiana O. (Educological discourse, 2014)
The article explores the genesis of the system of "rolling sculpture" of E. Jaques-Dalcroze school and its functioning in various educational institutions of the past and present; historical background of the formation and development of rhythm as part of the system of «art movement» and means of musical and choreographic education are analyzed; the place and role of rhythm as a musical-pedagogical disciplines in various forms of continuous choreographic education is stated; its essence, purpose, tasks and content is disclosed.